2021
DOI: 10.1038/s41431-021-00967-x
|View full text |Cite
|
Sign up to set email alerts
|

Familial cleft tongue caused by a unique translation initiation codon variant in TP63

Abstract: Variants in transcription factor p63 have been linked to several autosomal dominantly inherited malformation syndromes. These disorders show overlapping phenotypic characteristics with various combinations of the following features: ectodermal dysplasia, split-hand/foot malformation/syndactyly, lacrimal duct obstruction, hypoplastic breasts and/or nipples, ankyloblepharon filiforme adnatum, hypospadias and cleft lip/palate. We describe a family with six individuals presenting with a striking novel phenotype ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
1
7
0
1
Order By: Relevance
“…These disorders represent a challenging example of how defects in a single gene can be associated with a broad range of phenotypic variability. Consequently, recent data from other groups [11], together with data generated from the two present cases, provide support for the use of a merged molecular and clinical classification of those diseases that are associated with TP63 variants. Therefore, to overcome the diverse and confusing nature of the terminology that has been applied in the field to date, we propose the use of the term TP63-associated disorder, in combination with a thorough description of the respective phenotypes, in particular the presence or absence of cutaneous symptoms.…”
Section: Clinical Lettersupporting
confidence: 66%
“…These disorders represent a challenging example of how defects in a single gene can be associated with a broad range of phenotypic variability. Consequently, recent data from other groups [11], together with data generated from the two present cases, provide support for the use of a merged molecular and clinical classification of those diseases that are associated with TP63 variants. Therefore, to overcome the diverse and confusing nature of the terminology that has been applied in the field to date, we propose the use of the term TP63-associated disorder, in combination with a thorough description of the respective phenotypes, in particular the presence or absence of cutaneous symptoms.…”
Section: Clinical Lettersupporting
confidence: 66%
“…It has been proposed that GTAp63α may be the TAp63α equivalent in testes, with a role in the maintenance of germ cell integrity (Beyer et al, 2011). Whether the TA*p63α isoform has an important role in development remains to be elucidated, however, the recent identification of a variant affecting the unique N‐terminus of this isoform that associated with familial cleft tongue indicates a biological role (Schmidt et al, 2021). Although we identified a rare heterozygous missense variant affecting this isoform alone in a POI patient, our functional studies were not able to demonstrate any deleterious impact on TA*p63α conformation or activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to have greater activation and greater repression due to its extended N terminus (Pitzius et al, 2019) but its relevance to human biology is yet to be established. Recently a TP63 variant affecting only this isoform of p63 was found to cause furrowed tongue, implicating a role of TA*p63 in development (Schmidt et al, 2021), but whether it also has a role in oocyte integrity remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…It can be detected on the mRNA level in different cells and at the protein level for example in the SUM159 cancer cell line [ 198 ]. Interestingly, a recent publication has shown that mutation of the start codon of TA*p63α causes a syndrome in human patients characterized by cleft tongue and muscular hypotonia, suggesting that the TA* isoforms might play a role during development [ 199 ].…”
Section: Isoformsmentioning
confidence: 99%